Detection of Ochratoxin A using Cellulose Acetate Nanofibers Modified with Silver Nanoparticle - Al-Dhahebi, A.M. (Institute of Electrical and Electronics Engineers Inc., 2021)
Electrospinning is a viable and cost-effective technique capable of fabricating excellent nanofibrous structures with desired features such as large active sites, porous morphology, and electrochemical properties that suit and enable efficient biosensor platforms. Herein, an efficient electrochemical biosensor using electrospun cellulose acetate (CA) modified with silver nanoparticles has been developed for the detection of highly hazardous ochratoxin A (OTA). The obtained nanofibers were modified by the layer-by-layer assembly using chemical linkers and biorecognition elements. The developed biosensor shows excellent sensitivity and a low detection limit of 10 pM. It also demonstrates a good affinity towards OTA in cross-specificity studies. The proposed sensor is a potential platform for food monitoring as it opens new prospects towards the use of electrospun nanofibers modified AgNPs to enhance electrons movements and enable the fabrication of novel biosensors with improved functionalities. Â© 2021 IEEE.